McKeachie's teaching tips : strategies, research, and theory for college and university teachers - Svinicki, Marilla D., 1946-; McKeachie, Wilbert J., 1921-; McKeachie, Wilbert James, 1921- McKeachie's teaching tips (Belmont, CA. : Wadsworth, Cengage Learning)
Includes bibliographical references (p. 346-373) and index